2019
DOI: 10.1007/s42452-019-0678-y
|View full text |Cite
|
Sign up to set email alerts
|

Texture classification using convolutional neural network optimized with whale optimization algorithm

Abstract: Texture classification is an active area of research in the field of pattern recognition. Convolutional neural networks (CNNs) have a remarkable capability of recognizing patterns and are one of the most efficient deep learning techniques. But, finding the optimal values of the different hyperparameters of the CNN is a major challenge. Nature-inspired algorithms (NIAs) are the meta-heuristic algorithms well-known for their optimizing capability. Whale optimization algorithm (WOA) is a recent nature-inspired al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The CNN has its origin in the biological science domain for purpose classification tasks [6]. It is considered to be a special neural network because of its kind of arrangement in terms of full weight sharing.…”
Section: Overview Of Convolutional Neural Networkmentioning
confidence: 99%
“…The CNN has its origin in the biological science domain for purpose classification tasks [6]. It is considered to be a special neural network because of its kind of arrangement in terms of full weight sharing.…”
Section: Overview Of Convolutional Neural Networkmentioning
confidence: 99%
“…The meta-heuristic optimized CNN classifier was then used for classifying skin cancer images and confirmed that the procedure improved the accuracy of the CNN. Dixit et al 72 optimized CNN through WOA at the convolutional and fully connected layers to recognize texture. This approach aimed to optimize the values of the filters and the values of the weights and biases.…”
Section: Metaheuristic Algorithms and Related Workmentioning
confidence: 99%
“…Among many applications already using WOA there are some that utilize it in other deep learning field. Dixit et al proposed applying Whale Optimization Algorithm in convolutional neural network architecture in the texture classification task [ 19 ]. WOA has been employed for optimizing values of the filters in convolution layers as well as for weights and biases optimization in fully-connected ones.…”
Section: Introductionmentioning
confidence: 99%